Novel One-Pot Synthesis of Thiophenols from Related Triazenes under Mild Conditions - Khazaei, Ardeshir; Kazem-Rostami, Masoud; Moosavi-Zare, Ahmad Reza; Bayat, Mohammad; Saednia, Shahnaz (Synlett, 2012)
In this work, at first, triazenes were synthesized from primary aryl amines. Afterwards, triazenes were converted into the corresponding thiophenols in one-pot using sodium sulfide in acidic media, by in situ generation of diazonium counterion beside hydrogen sulfide as anionic sulfur nucleophile at room temperature. The procedure can be a convenient shortcut for the preparation of thiophenols from primary aryl amines.
Keywords: thiophenol; aryl amine; triazene; diazonium salt; one-pot synthesis